Efficiency of Ventilator Associated Pneumonia Prevention Protocol in a mixed intensive care unit in Pahang, Malaysia - Mat Nor, Mohd Basri; Abdul Rani, Mohammed Fauzi (2006)
Introduction Ventilator-associated pneumonia (VAP) rate in adult ICU varies between 8.0 and 46.3 episodes/1000 ventilator days. A National Audit of Adult Intensive Care Units (NAICU) in 2003 reported a high incidenceof 26.9/1000 ventilator days. A subsequent multiple one day prevalence study found a high VAP rate (42.8/1000 ventilator days) in our ICU in Kuantan. We developed an ICU guidelines called Ventilator Associated Pneumonia Prevention Protocol (VAPP) and conducted a study to asses the efficiency of VAPP in our ICU setup. Methods This comparative study was done in Hospital Tengku Ampuan Afzan (HTAA). The following data were collected pre (from 1st April to 31st March 2004) and post (from 1st September 2004 to 31st August 2005) VAPP: patients’ demographics, medical history, both hospital and ICU admissions and discharges dates, SAPS II scores, admission categories, organ failures, status on ICU and hospital discharge, duration on mechanical ventilation. Results There were a total of 941 patients in pre (n=480) and post (n=461) VAPP periods. Patients’ demographics, SAPS II scores and premorbid states were similar in both. VAP rate was 21.9/1000 ventilator days (37 episodes over 1689 ventilator days) pre VAPP and 8.35/1000 ventilator days (14 episodes over 1676 ventilator days) post VAPP. The relative risk reduction of VAP post implementation of VAPP was 68% with p value < 0.0001. When we look at the NNIS benchmarking on ventilator-associated pmeumonia for quality improvement, the incidence of VAP pre guidelines was 21.9% and this is above 90th percentile of the NNIS benchmark. In the post guideline group, the incidence of VAP has been reduced to 25th percentile. There was also a reducing trend of gram positive organisms as the cause of VAP in the post VAPP group.